Bridging and bonding: The roles of brokerage and closure in mobilizing support provision in online support groups - Sanguk Lee; Tai-Quan Peng (PLoS ONE, 2025)
Social capital theory suggests that network structure influences human behavior. Based on this premise, this study investigates how two distinct network structures—brokerage and closure—affect support provision in Online Support Groups (OSGs). Twelve years of data were collected from an online cancer community based in South Korea. Using computational methods, we measured support behaviors, network structures, and social capital. The findings reveal that brokers, through exposure to non-redundant information, provide social support in larger volumes, with higher quality, and in a more timely manner. While closure has limited explanatory power for overall support behaviors, it specifically facilitates provision of improved quality of emotional support through one’s enhanced trust. Additionally, the results highlight the importance of recognizing the dynamic developmental stages of OSGs to fully understand the social mechanisms driving support provision. These findings offer significant insights into the mobilization of social support through network structures in the OSG context.